Analysis of Student Satisfaction with Google Scholar Services as Reference using the Delone and Mclean Method - Permata, Nur Fitria Mita; Syaifullah, Syaifullah; Ahsyar, Tengku Khairil; Jazman, Muhammad (Sistemasi: Jurnal Sistem Informasi, 2024)
Google Scholar is a search engine that serves as a platform for finding references from sources like articles, books, and journals relevant to ongoing or planned research. It aids students in discovering references aligned with their research topics or discussions. Nevertheless, challenges such as technical glitches in Google Scholar's servers, internet connection problems, restricted or paid access to articles, and the search algorithm's potential misinterpretation of user queries can occur. This research seeks to assess information systems students' satisfaction with Google Scholar's services and evaluate user satisfaction using the DeLone and McLean model. The analysis results show that of the nine hypotheses tested, seven were supported and two were rejected. The study implies that to enhance Google Scholar in the future, adjustments should be made to better cater to the needs of users, particularly students, in locating relevant and accurate references.